Distribution of Poaceae family in Fars province, Iran - Jafarpour, Marjan; Mariapan, Manohar (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Although the plant species richness in Fars-Iran is high due to geological, soil and climatic variation, many species had yet to be identified. The species were identified using available lists on flora, monographs and other related sources. The distribution of Poaceae family, genera and species were mapped using a Geographical Information System (GIS) software. From the study, the Poaceae family has 90 genera and 170 species of which 5 are endemic. Of the 20 townships, Shiraz is highest in species richness.